ANALISIS PEMBENTUKAN PROVINSI TAPANULI TERHADAP PERCEPATAN PELAYAN PUBLIK UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Panjaitan, Jose Andreas; Pasaribu, Johnson; Tobing, Artha Lumban (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The establishment of Tapanuli Province is one way to improve public welfare through the acceleration of public services considering that the North Sumatra region is quite large and wide, so that areas far from the provincial capital experience obstacles in terms of provincial government services to the community, as a result, public welfare is always focused on areas around the city of Medan. This study aims to examine and analyze public services in the Tapanuli region, then the researcher conducts an analysis if the Tapanuli Province is formed, services to the community dealing with the provincial government will be easier to reach because the government will be close to each region. Then with the focus of the provincial government on the Tapanuli region, the government's responsiveness in handling all problems and issues between districts/cities will be faster, such as if there is a road between districts or damaged provincial roads, it will be quickly worked on and repaired. So with the existence of the Tapanuli Province, the workload of the North Sumatra Provincial Government will be reduced and the community will also find it easier to take care of all their affairs. Improving public services is one of the keys to driving the increase in the community's economy because a good bureaucracy is a bureaucracy that can be reached easily and quickly by the community.